Constraints to and prospects for sustainable livestock sector practices in Argentina with emphasis on antimicrobial usage - David Oseguera Montiel (South Centre, 2024)
Antimicrobial resistance (AMR) is a top threat for global health and development as it has the potential to become the next pandemic. Agriculture roughly accounts for three-quarters of all the antimicrobial usage. Modern animal husbandry systems use antimicrobials for disease prevention and growth promotion. Regulations and restrictions regarding antimicrobial use in agriculture vary across the regions of the world. This paper explores the situation of the Argentina livestock sector with regard to antimicrobial use. Argentina is renowned as a global food producer, notably for its grain and livestock production potential. This paper analyzes the constraints to and prospects for transitioning towards a more sustainable livestock farming production in Argentina by relying less on antimicrobials and without compromising productivity. The livestock sector in Argentina has embarked on the intensification of farming, especially beef farming, in the last thirty years. Farming intensification generally requires the use of greater quantities of antibiotics. Alternative sustainable intensification is necessary to overcome antimicrobial overuse. Various factors, including economic, social, and cultural, shape consumption patterns. The Argentine farming sector needs to focus on these context-specific situations, which will drive animal food production.
Keywords: 300; Agriculture; Animal Health; Animal Husbandry; Antibiotics; Antimicrobial Resistance (AMR); Antimicrobial Stewardship; Antimicrobials; Argentina; Farming; Food Animal Production; Food Production; Global Health; Health; Human Health; Livestock; Pandemic; Public Health; Sustainability